2022
DOI: 10.1111/eje.12842
|View full text |Cite
|
Sign up to set email alerts
|

Stress amongst dental students in the transition from preclinical training to clinical training: A qualitative study

Abstract: Objectives The present study sought to qualitatively evaluate third‐year undergraduate dental students' perceptions of sources of stress during the transition from preclinical to clinical training. Methods This was an observational, cross‐sectional, and qualitative study with a nonprobabilistic sampling design. The sample consisted of students in the third year of the five‐year undergraduate degree program in dentistry offered by the São Paulo State University (UNESP), School of Dentistry, Araraquara, São Paul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This may be due to the third year of the undergraduate course being where the transition between pre‐clinical training and clinical care occurs. According to de Souza Ferreira et al., 25 one of the main stressors during this phase is the difficulty of visualizing the operative field. Thus, loupes, regardless of the magnification level used, may have positively influenced the students’ visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the third year of the undergraduate course being where the transition between pre‐clinical training and clinical care occurs. According to de Souza Ferreira et al., 25 one of the main stressors during this phase is the difficulty of visualizing the operative field. Thus, loupes, regardless of the magnification level used, may have positively influenced the students’ visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, Deeb et al found that 40% of dental students in their sample encountered the criteria for burnout subscales ( Deeb et al, 2018 ). The beginning of clinical training and contact with patients are the main stressor agents for dental students ( de Souza et al, 2023 ). Female students report more anxiety than male students, and also the prevalence of trait anxiety seems to be higher in female students ( Blumer et al, 2019 ; Capdevila-Gaudens et al, 2021 ; Braz-José et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is in other words a relaxed, stable and comfortable posture with minimal muscles contractions. Neutral is applied here to indicate that the joints have a neutral area of movement that is avoids joints overstraining 17,18 . The dentist has the freedom to move in his balanced posture with no risk or harm; it does not require the operator a rigid posture 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Neutral is applied here to indicate that the joints have a neutral area of movement that is avoids joints overstraining 17,18 . The dentist has the freedom to move in his balanced posture with no risk or harm; it does not require the operator a rigid posture 18 . These movements are identified as active and passive balanced postures 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation